"Not-for-profit" leaders take a different route: Challenges facing the socially-oriented 'third sector'. Issue 2 (12th January 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – This paper examines some of the issues facing leaders of not-for-profit organizations, and considers ways in which this "third sector" is both similar to and different from the way that things operate in the public and private arenas. Practical implications: – This paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – This briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.